Safety with ocrelizumab in rheumatoid arthritis: results from the ocrelizumab phase III program. - Paul Emery; William Rigby; Paul P Tak; Thomas Dörner; Ewa Olech; Carmen Martin; Laurie Millar; Helen Travers; Elena Fisheleva (PLoS ONE)
Objective The objective was to determine the safety of ocrelizumab (OCR) in patients with rheumatoid arthritis (RA). Methods This was an analysis of the double-blind, placebo-controlled periods and long-term follow-up of 4 OCR phase III trials in RA (SCRIPT, STAGE, FILM and FEATURE). Safety data per study and the results of a meta-analysis of serious infectious events (SIEs) are presented. Results Overall, 868 patients received placebo, 1064 patients OCR 200 mg×2 (or 400 mg×1) (OCR200), and 827 patients OCR 500 mg×2 (OCR500) plus background methotrexate (MTX) at baseline and 24 weeks. During the double-blind, placebo-controlled periods, the incidence of adverse events and serious adverse events was comparable between the OCR+MTX and placebo +MTX groups. Infusion-related reactions were more common with OCR+MTX and decreased in frequency with subsequent infusions. Serious infusion-related reactions were rare (0.1%). Serious infections occurred more frequently with OCR500+MTX. In the meta-analysis, a statistically significant difference from placebo +MTX in incidence of SIEs per 100 patient-years of 2.4 (95% CI, 0.3-4.5) was observed with OCR500+MTX, but not with OCR200+MTX (0.6; 95% CI, -1.3 to 2.4). Patients recruited in Asia exhibited a higher risk of serious infections (hazard ratio, 1.78; 95% CI, 1.03-3.06). The incidence of human anti-human antibodies was <5%. Long-term follow-up indicated no differences in malignancy rates between the treatment groups. There was no apparent difference in time to B-cell repletion between the OCR dose groups. Conclusions In placebo-controlled clinical trials of RA, OCR500+MTX was associated with a higher risk of serious infections compared with placebo +MTX. The safety profile of OCR 200+MTX was comparable with placebo+MTX. Trial registration STAGE ClinicalTrials.gov NCT00406419 SCRIPT ClinicalTrials.gov NCT00476996 FILM ClinicalTrials.gov NCT00485589 FEATURE ClinicalTrials.gov NCT00673920.